2008
DOI: 10.1369/jhc.2008.951533
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase Interacting Protein 51 (PTPIP51) mRNA Expression and Localization and Its In Vitro Interacting Partner Protein Tyrosine Phosphatase 1B (PTP1B) in Human Placenta of the First, Second, and Third Trimester

Abstract: S U M M A R Y The cellular localization of protein tyrosine phosphatase 51 (PTPIP51) and its in vitro interacting partner protein tyrosine phosphatase 1B (PTP1B) was studied in human placentae of different gestational stages. The expression of PTPIP51 protein and mRNA was observed in the syncytiotrophoblast and cytotrophoblast layer of placentae from the first, second, and third trimesters. In contrast, PTP1B expression was restricted to the syncytiotrophoblast during all gestational stages. Cells of the cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The variability of the subcellular localization in the rat retina is in agreement with previous studies, which reported different localization for PTPIP51 according to the cell type, but also resulting from the phosphorylation status of PTPIP51 and from the type of the interacting proteins involved (Stenzinger et al, 2009b;Brobeil et al, 2010Brobeil et al, , 2012Bobrich et al, 2013). Furthermore, different isoforms of variable molecular weight have been observed in many tissues, including mouse brain and retina (Stenzinger et al, 2005(Stenzinger et al, , 2009aMaerker et al, 2008;Koch et al, 2009;Brobeil et al, 2010). Experimental findings were limited to Western blot analyses but predictive alternative splicing from bioinformatics analysis of the coding ORF of PTPIP51 could explain the generation of different PTPIP51 isoforms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The variability of the subcellular localization in the rat retina is in agreement with previous studies, which reported different localization for PTPIP51 according to the cell type, but also resulting from the phosphorylation status of PTPIP51 and from the type of the interacting proteins involved (Stenzinger et al, 2009b;Brobeil et al, 2010Brobeil et al, , 2012Bobrich et al, 2013). Furthermore, different isoforms of variable molecular weight have been observed in many tissues, including mouse brain and retina (Stenzinger et al, 2005(Stenzinger et al, , 2009aMaerker et al, 2008;Koch et al, 2009;Brobeil et al, 2010). Experimental findings were limited to Western blot analyses but predictive alternative splicing from bioinformatics analysis of the coding ORF of PTPIP51 could explain the generation of different PTPIP51 isoforms.…”
Section: Discussionsupporting
confidence: 91%
“…A potential role of PTPIP51 in cell morphology and motility has been postulated in different cell lines via its interaction with the 14-3-3 adaptorscaffold protein (Yu et al, 2008). Moreover, PTPIP51 has been reported to be expressed in different ciliated epithelia such as the brain ependymal cells, the respiratory epithelium, the uterine epithelium or efferent ductules of the testis (Stenzinger et al, 2005(Stenzinger et al, , 2009a, where PTPIP51 protein appeared to be localized within the motile cilium, close to the microtubules and the basal body (Stenzinger et al, 2005). Considering that the outer segment of the photoreceptor is a modified cilium (Adams et al, 2007;Kennedy and Malicki, 2009;Pearring et al, 2013;Guemez-Gamboa et al, 2014), it might be possible that PTPIP51 participates in the regulation of the dynamics of the connecting cilium or the intraflagellar transport machinery, occurring during both the outer segment morphogenesis and renewing.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal plasma does not simply protect sperm but can also influence the reproductive events independent of sperm in some species other than cattle. Seminal fluid regulation of female reproductive physiology is shown in hamsters, pigs, and human studies [ 68 , 73 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ]. Mating with males lacking seminal vesicles resulted in reduced blastocyst rate, reduced conception rates, and offspring that experienced sex-dependent phenotypic changes postnatally [ 120 , 125 , 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein tyrosine phosphorylation is involved in sperm-oocyte interaction, penetration, and fertilization [ 127 ]. Protein tyrosine phosphatase-interacting protein 51 (PTPIP51/RMD3) mRNA expression was seen in syncytiotrophoblast and cytotrophoblast layers of placentae and serves as cellular signaling partner in angiogenesis and vascular remodeling in women [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…One PTP, PTP-1B, was first isolated from human placental tissue (Tonks et al 1988) and has since been reported to be expressed at the protein level in the syncytiotrophoblast (Stenzinger et al 2008). In other systems, it regulates insulin and IGF signaling (Koren & Fantus 2007), but its function in the placenta is currently unknown.…”
Section: Tyrosine Phosphatasesmentioning
confidence: 99%